(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article explores the problem of socio-cultural identity in the context of intercultural dialogue, focusing on the Japanese experience as a unique model of cultural sustainability. In the era of globalization, intensified intercultural interactions create both opportunities for cultural enrichment and risks of identity transformation or erosion. The study aims to analyze how intercultural dialogue functions as a mechanism for the formation and preservation of sustainable identity. The research is based on a philosophical and interdisciplinary approach, combining theories of identity, intercultural communication, and cultural hermeneutics. Special attention is given to the dialogical nature of identity, which is formed through interaction with the “Other,” as well as to the role of ethical and aesthetic values in maintaining cultural continuity. The Japanese model is examined as an example of selective adaptation, where external influences are integrated without undermining the cultural core. Concepts such as harmony (wa), aesthetic sensitivity, and the synthesis of tradition and modernity are identified as key factors contributing to identity resilience. The findings demonstrate that intercultural dialogue, when grounded in cultural self-awareness and value-based selectivity, enhances rather than weakens socio-cultural identity. The Japanese experience offers important insights for other societies seeking to balance globalization and cultural preservation.